Brucellosis in mammals of Costa Rica: An epidemiological survey - Hernández Mora, Gabriela (2017)
Fondos del Sistema del Consejo Nacional de Rectores (FEES-CONARE FSI001). Scholarship: Ministerio de Ciencia, Tecnologı´a y Telecomunicaciones (MICITT-PINN) PND-033-15-2. The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript.